Integral Equations of Biharmonic Constant ?1 - Slope Curves according to Type-2 Bishop Frame in the Sol Space - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2013)
In this paper, we study biharmonic constant Pi(1) - slope curves according to type-2 Bishop frame in the SOL3. We characterize the biharmonic constant Pi(1) - slope curves in terms of their Bishop curvatures. Finally, we find out their explicit parametric integral equations in the SOL3.
Keywords: type-2 Bishop frame; SolSpace; Curvatures